Anion-mediated pathways in organophosphate degradation in the Oconee River watershed in Georgia - Grace Stamm; Gayatri Basapuram; Srimanti Duttagupta; Avishek Dutta (Emerging Contaminants, 2025)
The degradation of organophosphate pesticides in aquatic ecosystems is influenced by various environmental factors. This study investigates the influence of nitrate, sulfate, and phosphate on the degradation of malathion, a commonly used organophosphate pesticide, in the North Oconee River watershed in Georgia. Microcosm experiments were conducted to simulate environmental conditions and assess both microbial and non-microbial transformation pathways. Nitrate, sulfate, and phosphate were found to enhance malathion degradation through microbially mediated oxidative and hydrolytic pathways. The presence of mercuric chloride, which suppressed microbial activity, resulted in slower degradation rates across all conditions, underscoring the pivotal role of microbial communities in pesticide transformation. Non-targeted analyses identified key degradation products, including malaoxon, succinic acid, and diethyl succinate, primarily under nitrate and sulfate conditions, supporting the involvement of these anions in the degradation process. These findings highlight the complex interactions between nutrient dynamics and pesticide persistence, offering valuable insights for sustainable water management and pollution control in agro-impacted freshwater systems.